A study of the misuse of Sūratu Yāsīn among Yoruba Muslims - Adetona, Lateef Mobolaji (Ilorin journal of religious studies, 2016)
The Glorious Qur'ān apart from serving the purpose of guidance also serves many other purposes to the Muslims, two of which are supplication and healing. Evidences of this assertion abound in both the Qur'ān and the Sunnah. Muslim scholars across the world have explored the Qur'ān with the aim of proffering solutions to all problems ranging from spiritual, physical and psychological. They have always believed that the Qur'ānic passages are quite potent and efficacious. One of such passages of the Qur'an is Sūratu Yāsīn. This study therefore takes a look at the hidden spiritual properties of the sūrah namely its merits, benefits and virtues. The various ways by which contemporary Yoruba Muslims put it to use are equally examined. The study reveals out that while righteous Muslims have always employed it for good ends, the fickle and vicious ones employ it for diabolical ends.